Retina fundus image mask generation using pseudo parametric modeling technique - Aibinu, Abiodun Musa; Salami, Momoh Jimoh Emiyoka; Shafie, Amir Akramin (IIUM Press, 2010)
This paper discusses a new pseudo modeling technique for the generation of retina fundus image (RFI) mask. The model coefficients necessary for the generation of the mask has been estimated from the synaptic weights of real-valued neural network. Performance analysis of the newly proposed three step technique has been evaluated using DRIVE databases and other RFI obtained from other sources. he accuracy obtained by the application of the proposed technique on RFI contained in the DRIVE database varies between 99.62% and 99.97%.